Dinámica y determinantes del crecimiento en el sector vivienda en Colombia: análisis empírico durante el periodo 1997-2013 (2014)
This research work presents, first of all, the result of an analysis of the main determinants of both demand and supply of housing, which ultimately give a description of the behavior and general situation of the construction sector. Subsequently, by means of a cointegration model, the behavior of the determining variables is verified, in addition to showing a long-term trend in both supply and demand with the GDP of the construction sector.